Pelatihan Baca Kitab Akhlāq Al-Nisā’ di Desa Kotah Kec. Jrengik Kab. Sampang - Takwallo (Jurnal Masyarakat Mengabdi Nusantara, 2022)
The formulation of the problem raised in this community service activity is regarding the lack of knowledge of the community in Kotah Village, Kec. Jrengik Kab. Confused about women's morals that really must be understood in the study of the book Akhlāq al-Nisa', what are the virtues that women have, things that a woman must do and avoid and what threats a woman will get if she violates the Shari'a ' in the Islamic religion. To find alternative solutions to the above, a study of the Akhlāq al-Nisa' book was held in an effort to improve the quality of students and students in reading the yellow book in Kotah Village, Kec. Jrengik Kab. Lacquer. The objectives of this PKM activity are: 1. To equip students and students with knowledge in reading the yellow book 2. To improve the quality and knowledge of students and students in reading the book. The problem solving framework designed in PKM activities in the form of implementing this training activity is: 1. Periodic explanation of materials. 2. Conduct book reading exercises using the book Akhlāq al-Nisā' every Wednesday night which is weekly. Based on interviews, question and answer and direct observation during the activity, this community service activity yielded the following results: first, increasing the knowledge of students and students in reading the yellow book, second is increasing the quality and knowledge of students and students in reading the book, third is increasing knowledge and Community morals.